Body composition and strength of basketball players - Aleksic, A.; Majkic, B. (23rd International Scientific Conference "FIS COMMUNICATION 2021", 2021)
Basketball, as a team sport, requires a developed physical readiness in order to play a game successfully. In addition, motor abilities, changes in body composition and the growth of the body with maturation greatly affect the basketball game. The aim of the study was to determine how body composition affects the strength of basketball players. Nineteen basketball players, aged 14.10±0.55 years, with a sports experience of 6.77±1.25 years, participated in the research. All subjects were clinically healthy and had no serious injury in the last six months until the day of testing. Body composition (body height, body mass, body fat percentage, muscle mass percentage and body mass index) was determined using Omron BF511 bioimpedance device (Omron Healthcare Co., Kyoto, Japan) and Martin`s anthropometer GPM 101 (GPM GmbH Switzerland). Explosive, repetitive and static strength were tested, with the help of specific tests. The relationship between body composition and strength was assessed using Pearson's coefficient of correlation and the statistical significance was set at p<0.05. Statistical procedures and analyses were performed using the statistical program IBM SPSS Statistics 20.0. The results of this study show a high correlation of body composition with strength variables. The greatest responsibility for the relationship among the variables had the results of body mass index (p<0.01, p<0.02, p<0.05), body fat percentage (p<0.02, p<0.05), then, body weight (p<0.02, p<0.03) and the variable that has the lowest correlation with strength variables is the percentage of muscle mass (p<0.05). The results of this study show a negative correlation between body mass index, body mass and body fat percentage with all strength variables, which proves that higher parameters of the previously mentioned variables, have decrease the effect on strength performance. One static strength variable was positively correlated with the percentage of muscle mass and this proved that a higher percentage of muscle can improve a certain part of static strength.